Thriving @ Work: Leveraging the Connection between Well-Being and Productivity. - Hubbard, Joey; Huffington, Arianna (linkedin.com, 2018)
Continue your Thrive journey. Arianna Huffington and Joey Hubbard discuss how well-being can contribute to your productivity and success at work.